Implantación de la contabilidad de costos por lotes de producción en la panadería “The Paulas´S Bakery” periodo octubre - diciembre 2012 - Ludeña Bustán, Elizabeth Patricia (2014)
This thesis is related to the implementation of cost accounting batch production of artisanal bakery "THE PAULAS 'S BAKERY "Loja City, between October December 2012", by not having an accounting real information that allows profitability in every product. The objectives were met through the implementation of cost accounting batch production was collected pertinent to begin the same information, plan and manual accounts, initial inventory used throughout the accounting process was developed to obtain the financial statements and the actual cost of each product. The methodology used in developing thesis documentary field has been directed towards a descriptive level, was collected and organized information to interpret all data in the enterprise; emphasizing the main elements of the system cost batch production. The results obtained in the process allowed the development of the cost accounting system batch production, in order to allow measure, quantify and define the cost of an asset, in order to fulfill the mission and vision, new perspectives have compete in the market. Finally conclusions and recommendations and the implementation of the accounting system that will deliver results that help determine projections firmly in the bakery "The Paulas 's Bakery " and become an important contribution to the economic development of the province of Loja arises.